THE ILLOCUTIONARY ACT IN SUSILO BAMBANG YUDHOYONO TWEET IN TWITTER - Boediman HM Sitohang; Lidiman Sahat Martua Sinaga (State University of Medan, 2014)
ABSTRACT This research focused on illocutionary act used in Susilo Bambang Yudhoyono tweet in twitter. The research was conducted by using qualitative research method. The data were collected from the twitter account of Susilo Bambang Yudhoyono. The findings of the thesis shows that there are 191 occurrences of illocutionary act which classified into five types of illocutionary act. They were declarative (5), representative (112), expressive (36), directive (32), and commissive (6). The most dominant type of illocutionary act that used in Susilo Bambang Yudhoyono Tweet in Twitter was representative with (58,63%). Representatives became the most dominant types of illocutionary act because most of Susilo tweets were informs, reports, describes, and claims. The implication is Susilo needs to inform the people about his work so that they know what ever he did and as he said the purpose of making twitter account is to hear people aspiration so he informs his people and people will support him. Keywords: Illocutionary Act, Tweet, Twitter.